Intuitive Vision and Indigenous Immunity Boosting approaches for COVID19: From the Literature of Pandit Shriram Sharma Acharya - Rahul Kumar Satuna; Aradhana Negi; Ravindra Satuna (Dr. Chinmay Pandya, 2020)
The need of the hour, in COVID19 crises, is to take care of the health from all aspects. A huge population of the world has not been only infected by Corona Virus but also a considerable number of persons have been deceased due to the acute symptoms of COVID19.  As far no vaccine or approved medicine for COVID19 has been found by any country to date. So, the only weapon left to break the chain of the infection is to follow the precaution strategy given by various health experts. Along with precautions such as social distancing, wearing masks and gloves etc., the health experts have also revealed that weak immunity is the prime factor to come in the grip of the Corona Virus. In this research paper, the intuitive vision and indigenous immunity-boosting approaches from literature of visionary scholar Pandit Shriram Sharma Acharya from India, relevant to the pandemic state, have been compiled. The reason to focus on the writings of Pandit Shriram Sharma Acharya is his featured knowledge of the health sector. One hundred twenty-five books out of thirty-two hundred books written by him are focused on various aspects of human health, which actually, is a boon for humanity and society.